Novel device for assisted vaginal birth: using integrated qualitative case study methodology to optimise Odon Device use within a feasibility study in a maternity unit in the Southwest of England. Issue 8 (4th August 2022) - Hotton, Emily J; Blencowe, Natalie S; Bale, Nichola; Lenguerrand, Erik; Draycott, Tim J; Crofts, Joanna F; Wade, Julia
Abstract : Objective: When novel devices are used 'in human' for the first time, their optimal use is uncertain because clinicians only have experience from preclinical studies. This study aimed to investigate factors that might optimise use of the Odon Device for assisted vaginal birth. Design: We undertook qualitative case studies within the ASSIST Study, a feasibility study of the Odon Device. Each 'case' was defined as one use of the device and included at least one of the following: observation of the attempted assisted birth, and an interview with the obstetrician, midwife or woman. Data collection and thematic analysis ran iteratively and in parallel. Setting: Tertiary referral National Health Service maternity unit in the Southwest of England. Participants: Women requiring a clinically indicated assisted vaginal birth. Intervention: The Odon Device, an innovative device for assisted vaginal birth. Primary and secondary outcome measures: Determining the optimal device technique, device design and defining clinical parameters for use. Results: Thirty-nine cases involving an attempted Odon-assisted birth were included in this study, of which 19 resulted in a successful birth with the device. Factors that improved use included optimisation of device technique, device design and clinical parameters for use. Technique adaptations included: applying the device during, rather than between, contractions; having a flexible approach to the application angle; and deflating the air cuff sooner than originally proposed. Three design modifications were proposed involving the deflation button and sleeve. Although use of the device was found to be appropriate in all fetal positions, it was considered contraindicated when the fetal station was at the ischial spines. Conclusions: Case study methodology facilitated the acquisition of rapid insights into device function in clinical practice, providing key insights regarding use, design and key clinical parameters for success. This methodology should be considered whenever innovative devices are introduced into clinical practice. Trial registration number: ISRCTN10203171 .